(untitled) (Lundiana: International Journal of Biodiversity, 2008)
The wading bird communities in lacunar systems are mainly structured based on the availability and distribution of feeding resources and appropriate conditions for their reproduction and establishment. As a result, in a given habitat, each species selects, according to the possibilities of its behavioral repertoire, the best way to explore the available resources. In this work, we investigate aspects of habitat selection and diurnal activity of seven species at Lagoa da Pampulha, an artificial lake situated in the metropolitan region of Belo Horizonte, Minas Gerais State, Southeast Brazil. The data was taken through the study of interference of some biotic and abiotic variables on the community dynamics. The results showed a segregation of the species in guilds, in accordance with the patterns of preference or rejection of habitats, partially reflecting the method used by them in resource exploration. In this context, four groupings are considered: (1) Dendrocygna viduata and Amazonetta brasiliensis; (2) Ardea alba and Phalacrocorax brasilianus; (3) Ceryle torquatus and Chloroceryle amazona; and (4) Egretta thula. Moreover, regarding the studied variables, the species segregate mainly as a function of the presence or absence of aquatic plants and water quality. In general, the depth of the water column was a secondary factor in the choice of habitat. However, depending on the species, these variables presented different degrees of interference in this choice. With relation to the activity period of each species, there is a great diurnal variation in the activity patterns, particularly in the hours of larger incidence of solar radiation, suggesting a bimodal rhythm of activities.